Baby Massage On The Development Of Gross Motor Skills In Infants At 3-6 Months Of Age - Indah Dewi; Mayang Wulan; Suyanti Suwardi; Utary Dwi Listiarini (Jurnal Maternitas Kebidanan, 2026)
Infant development according to their age shows that 52.5% experience gross and fine motor disorders. Lack of stimulation in infants can cause developmental delays that impact subsequent stages. Several factors influence gross motor development, including biological, environmental, health, and psychosocial factors. The recommended stimulation is baby massage. This study aims to determine the effect of baby massage on gross motor development in infants aged 3-6 months at Midwife Sehati's Private Practice. This study uses a quasi-experimental design with a pre-test and post-test approach without a control group. The population of this study consists of 30 infants aged 3-6 months, and the sample includes 15 infants selected through purposive sampling. Baby massage is performed for 4 weeks with a frequency of twice a week. Data analysis in this study uses the Wilcoxon test. The study of the results showed that before the intervention, 15 infants (100%) had motor development categorized as questionable. After the baby massage intervention, 13 infants (86.7%) were categorized as normal, and 2 (13.3%) were questionable. The Wilcoxon test results with a p-value of 0.000 (<0.05) indicated that the hypothesis was accepted, suggesting that baby massage has a significant effect on gross motor development in infants aged 3-6 months at PMB Sehati Medan in 2026. The conclusion, baby massage performed by the researcher can support gross motor development in infants. It is suggested that healthcare professionals provide baby massage counseling to support gross motor development in infants.